2017
DOI: 10.12991/marupj.300814
|View full text |Cite
|
Sign up to set email alerts
|

Kuersetinin Cu(II) ve Al(III) Komplekslerinin Potansiyometrik ve Kromatografik İncelenmesi

Abstract: In this study, the stability constants of the copper(II) and aluminium(III) complexes of quercetin were determined potentiometrically by using Calvin-Bjerrum and Irwing Rossotti methods. The protonation constants of quercetin were found:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The cancer preventive and therapeutic effects of quercetin have been demonstrated through in vitro as well as in vivo experimental findings [21,22]. As depicted in Scheme 1, Que consists of three phenolic rings (A, B, and C rings); it has three available sites for metal chelation including ortho-dihydroxyl (catechol) group of the B ring (site A), 5-hydroxy-4-keto group (site B), and 3-hydroxy-4keto group (site C), since both hydroxyl and keto groups of Que have the ability to form metal complexes [23][24][25][26][27][28][29][30][31][32][33][34][35]. Interestingly, it was observed that some biological properties of quercetin such as antioxidant, antibacterial, and antitumor activities, change with metal chelation.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The cancer preventive and therapeutic effects of quercetin have been demonstrated through in vitro as well as in vivo experimental findings [21,22]. As depicted in Scheme 1, Que consists of three phenolic rings (A, B, and C rings); it has three available sites for metal chelation including ortho-dihydroxyl (catechol) group of the B ring (site A), 5-hydroxy-4-keto group (site B), and 3-hydroxy-4keto group (site C), since both hydroxyl and keto groups of Que have the ability to form metal complexes [23][24][25][26][27][28][29][30][31][32][33][34][35]. Interestingly, it was observed that some biological properties of quercetin such as antioxidant, antibacterial, and antitumor activities, change with metal chelation.…”
Section: Flavonoidsmentioning
confidence: 99%